Radiofrequency thermocoagulation for V2/V3 idiopathic trigeminal neuralgia: effect of treatment temperatures on long-term clinical outcomes: A Cohort Study. Issue 26 (June 2016) - Yao, Peng; Deng, Yi-yong; Hong, Tao; Wang, Zhi-bin; Ma, Jia-ming; Zhu, Yong-qiang; Li, Hong-xi; Ding, Yuan-yuan; Pan, Shi-nong
Abstract : Abstract: Radiofrequency thermocoagulation (RFT) is widely used to treat trigeminal neuralgia (TN); however, the optimal temperature at which RFT is most efficacious remains under much debate. Thus, the aim of the present study was to determine the lowest temperature at which morbidity could be minimized and patient outcomes maximized. A multivariate analysis was used to study 1354 patients who underwent computed tomography (CT)-guided RFT for V2/V3 idiopathic trigeminal neuralgia (ITN) during from June 2006 to May 2015. RFT was carried out at 62, 65, and 68°C, while keeping all other RF parameters the same. This was a prospective cohort study, in which we assessed intra- and postoperative complications, pain relief, and long-term health-related quality of life (HRQoL). The intraoperative and in-hospital complications of patients were mainly facial hematoma, mouth and external auditory meatus penetration, nausea, vomiting, dizziness, and headache, which were all treated symptomatically. In long-term follow-up, patients with pain relief (defined as no pain and no required drug intervention) at 62, 65, and 68°C accounted for 94.2%, 98.3%, and 98.8% (at discharge); 83.8%, 90.1%, and 91.4% (at 1 year); 66.7%, 80.5%, and 88.2% (at 3 years); 59.0%, 64.3%, and 77.2% (at 5 years); 48.7%, 57.8%, and 72.3% (at 7 years); 40.6%, 53.7%, and 60.3% (at 9 years), respectively. The number of patients with facial numbness, masticatory atonia, or corneal hypoesthesia was increased with the elevation of temperature, but these complications were all mild. No blindness, deafness, intracranial hemorrhage, or death as a result of the surgical intervention occurred in any patients. SF-36 scores showed highest HRQoL in the group treated at 68°C, followed by the 65 and 62°C groups, respectively. Our results demonstrate that 68°C is a good choice for RFT of V2/V3 ITN. The alternative option is 65 or 62°C for RFT to minimize the occurrence of complications including facial numbness, yet which often yields a higher recurrence rate.